Evaluation of essential oil on the growth in vitro and in vivo of anthracnose in 'Hass' avocados - Muniz, A. C.C. [UNESP]; Marques, K. M. [UNESP]; Galati, V. C. [UNESP]; Pereira, F. D. [UNESP]; Mattiuz, B. H. [UNESP]; Glória, E. M.; Mattiuz, C. F.M. (International Society for Horticultural Science (ISHS), 2016)
The objective of this study was to evaluate the postharvest effects of essential oils on the in vitro and in vivo growth of the causal agent of anthracnose in postharvest avocado 'Hass'. Nine essential oils were tested for their antifungal potential by the method of assessing the minimum inhibitory concentration. The fungal species evaluated in this study was C. gloeosporioides isolated from naturally infected avocados. Among the tested oils, it stood out the oil extracted from the Thymus vulgaris specie that presented the minimum inhibitory concentration for the fungus of 0.046%. In in vitro step, the thyme oil was added to the culture medium at doses of 0; 10; 50; 100; 200; 500 and 1000 μL L-1. It was performed six replications per treatment. In in vivo step, the avocados were inoculated with conidial suspension of C. gloeosporioides and immersed for 1 min in thyme essential oil associated with a commercial wax at concentrations of 200; 500 and 1000 μL L-1. After, the fruits were stored at 12±2°C and 80±3% RH for 14 days, and at 22±2°C and 80±5% RH for three days. The thyme oil at concentrations of 200; 500 and 1000 μL L-1 inhibited the mycelial growth of C. gloeosporioides in vitro, whereas the concentrations of 500 and 1000 μL L-1 were more effective in reducing the severity and incidence of the disease, the respiratory rate and the ethylene production and the loss of weight by the fruits, indicating that the thyme essential oil in these doses presents itself as an alternative for the control of anthracnose in the postharvest of avocado 'Hass'.
Keywords: Colletotrichum gloeosporioides; Disease; Natural products; Persea americana; Thymus vulgaris